Automotive after-sales service quality attributes and customer loyalty: an empirical study of Malaysian National carmakers / Zainil Hanim Saidin ... [et al.] - Saidin, Zainil Hanim; Yusoff, Rushami Zien; Mohd. Mokhtar, Sany Sanuri; Saad, Rohaizah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
The purpose of this paper is to explore on the uni-dimensionality of service quality and how the different attributes influence the level of customer loyalty. A modified SERVQUAL instrument was used to capture customers' perceptions of service quality. Adapting the dimensions from the literature and tested in the context of Malaysian national automotive after-sales service, PLS-SEM was used to investigate the influences of the modified dimensions of service quality attributes on customer loyalty. The results of the study provide strong support for the predictive power of perceived service quality on customer loyalty and shows that customer service is the most important dimension to explain service quality. Support service is also the significant contributor, and correlated with the smallest weight. The findings provide an insight not only to the national carmakers as the main subject of evaluation, but also valuable to the ordinary workshops that offer similar service and maintenance for vehicles. The empirical evident may facilitate the workshop as an entrepreneur to properly understand the importance of excellent quality of service and high quality of customer-service provider relationship in ensuring long-term business sustainability.